1987
DOI: 10.1159/000275943
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology and Prognosis of Sudden Deafness with Special Reference to the N<sub>1</sub> Latency

Abstract: Electrocochleography (ECochG) was performed in 84 patients with sudden deafness which were classified into 3 groups according to the ECochG findings, i.e. the unchanged N1 latency, the prolonged N1 latency and the absence of N1 response. The cause of hearing loss in the first group was thought to be strial, postsynaptic or mild cochlear damage and that in the second to be vascular, sensory or neural damage. The first group showed a better prognosis than those of the other two.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…It is difficult to estimate the efficiency of the various treatment modalities used in sudden hearing loss 6 , 7 . The factors considered to be important in the prognosis of this condition are: severity of hearing loss, duration of symptoms before treatment, presence of vertigo, type of audiogram, age of patient, hearing level in the opposite ear, erythrocyte sedimentation rate, coexistence of metabolic diseases such as hypertension and diabetes mellitus, and audiological parameters 2 , 8 – 12 …”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to estimate the efficiency of the various treatment modalities used in sudden hearing loss 6 , 7 . The factors considered to be important in the prognosis of this condition are: severity of hearing loss, duration of symptoms before treatment, presence of vertigo, type of audiogram, age of patient, hearing level in the opposite ear, erythrocyte sedimentation rate, coexistence of metabolic diseases such as hypertension and diabetes mellitus, and audiological parameters 2 , 8 – 12 …”
Section: Introductionmentioning
confidence: 99%
“…Electrocochleography of patients with SD has shown that the patients who had a normal latency for N 1 all recovered completely, but in cases with an increased latency or missing N 1 the prognosis was worse [61].…”
Section: Studies On Patients With Sdmentioning
confidence: 99%
“…It has been discussed which is more involved in SD, the inner ear or the retrocochlear locations (5)(6)(7)(8)(9). Portmann et al (5) reported that retrocochlear dysfunction was involved in some SD cases as determined by electrocochleography (ECochG).…”
Section: Introductionmentioning
confidence: 99%
“…Portmann et al (5) reported that retrocochlear dysfunction was involved in some SD cases as determined by electrocochleography (ECochG). Ikeda et al (6) divided SD cases into three groups based on N 1 latency in the ECochG. However, it is considered difficult to determine the primary site involved based on only the compound action potential (CAP) findings in ECochG.…”
Section: Introductionmentioning
confidence: 99%